Comparative Analysis of Model Reference Adaptive Controller in Steam Distillation Process for Essential Oil Extraction System - Kasuan, Nurhani; Hezri Fazalul Rahiman, Mohd; Nasir Taib, Mohd; Hafiz A. Jalil, Mohd; Abd Majid, Masmaria; Yasmin Abd Rahman, Farah (International Journal of Engineering and Technology, 2018)
This paper aims to study the Model Reference Adaptive Controller using MIT-Rule and Lyapunov applied in a pilot-scale steam distillation process. The control objective of MRAC is to regulate steam temperature in the distillation column for essential oil extraction system. A first-order auto-regressive exogenous (ARX) function is derived to represent steam temperature model for numerical experimentation and extended to real-time implementation. During the experiments, the MRAC MIT-Rule and Lyapunovâ€™s are tested with and without integral component in the controller structure. It shows that eliminating the integral give stable response and low steady-state error compared to MRAC with the integral. The MRACâ€“MIT controller has fast response and low SSE and RMSE compared to the MRACâ€“Lyapunov in both simulation and real-time experimentation.Â Â